2013
DOI: 10.1182/blood-2013-02-483511
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular NAD+ depletion enhances bortezomib-induced anti-myeloma activity

Abstract: Key Points• FK866 combined with bortezomib induces synergistic anti-MM cell death.• Addition of low doses of NAD1-depleting agent FK866 overcomes bortezomib resistance in MM cells.We recently demonstrated that Nicotinamide phosphoribosyltransferase (Nampt) inhibition depletes intracellular NAD 1 content leading, to autophagic multiple myeloma (MM) cell death. Bortezomib has remarkably improved MM patient outcome, but doselimiting toxicities and development of resistance limit its long-term utility. Here we obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 42 publications
(52 reference statements)
5
72
0
Order By: Relevance
“…It was previously shown that blockage of the NAD + salvage pathways using the NAMPT inhibitor FK866 induces autophagic death in neuroblastoma SH-SY5Y cells and multiple myeloma cells. [19][20][21] Recent data show that FK866 activates AMPK (adenosine monophosphateactivated protein kinase) and downregulates mammalian target of rapamycin (mTOR) signalling in hepatocarcinoma cells. 22 In view of the important role NAD + has in modulating p53 activity (via NAD + -dependent SIRTs) 23,24 and our recent demonstration that the NAD + synthesizing enzyme NMNAT2 is a downstream target of p53, 16 we wished to first determine if FK866-induced cell death was p53-dependent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was previously shown that blockage of the NAD + salvage pathways using the NAMPT inhibitor FK866 induces autophagic death in neuroblastoma SH-SY5Y cells and multiple myeloma cells. [19][20][21] Recent data show that FK866 activates AMPK (adenosine monophosphateactivated protein kinase) and downregulates mammalian target of rapamycin (mTOR) signalling in hepatocarcinoma cells. 22 In view of the important role NAD + has in modulating p53 activity (via NAD + -dependent SIRTs) 23,24 and our recent demonstration that the NAD + synthesizing enzyme NMNAT2 is a downstream target of p53, 16 we wished to first determine if FK866-induced cell death was p53-dependent.…”
Section: Resultsmentioning
confidence: 99%
“…The demonstration that similar results can be achieved by NAMPT KD confirms that NAMPT is specifically targeted by FK866. That inhibition of NAMPT (and hence the NAD + salvage pathway) results in autophagy and cell death has recently been reported; [20][21][22] however, the precise underlying mechanisms are unclear. Our results show that this is at least, in part, due to increased p73 levels as KD of p73 in FK866-treated cells effectively reverses the effects of FK866 on autophagy and cell survival.…”
Section: 33mentioning
confidence: 99%
“…While intracellular NAD + protects cells against PARP-1-dependent cell death and possibly also against some forms of apoptosis [59][60][61] and autophagy, 60,62 it has an opposite role in promoting necroptosis. NAD + may therefore represent an important intracellular factor regulating the choice of cell demise, a finding that may call for caution in the clinical translation of pharmacological and nutraceutical approaches Figure 7 Cambinol protects from renal ischemia/reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%
“…Nampt-targeting emerges as effective approach not only when coupled to standard chemotherapy, including DNA damaging agents [16] but also in combination with more modern, molecularly-targeted agents (such as ibrutinib, cyclosporin A and bortezomib) [8,9,13].…”
Section: Nampt Inhibitorsmentioning
confidence: 99%
“…As a result, Nampt inhibitors as monotherapy have demonstrated potent antitumor activity in preclinical cancer models [3][4][5][6][7]. In such a scenario, investigators have also tested NAD + -depleting agents in combination with antineoplastic agents, chemotherapy, or radiotherapy in a wide range of hematological malignancies, including AML, MM, and lymphomas, observing an increased activity and overall tolerability of these agents [8][9][10][11][12]. Thus, several clinical trials are currently exploring such metabolic vulnerability in patients undergoing chemotherapy (NCT02702492, NCT00435084, and NCT00431912).…”
mentioning
confidence: 99%